Can society learn from experience? Society as a subject - Giza, Anna (Journal of Public Governance, 2014)
The term “society” is usually used as the subject of various statements: “society tends to…”, “society does not trust politicians”, etc. Theoretically, however, individualism prevails both ontologically (“society” is a complex of individual actions) and methodologically. However, there exists a theoretical stance that considers society as an intention-driven agent, a self-reflective subject able to build the structures of self-knowledge. The paper discusses the consequences of adapting the “intentional stance” in the study of society.